A continuum model for heat and mass transfer in moving-bed reactors for thermochemical energy storage. (1st May 2022) - Korba, David; Huang, Wei; Randhir, Kelvin; Petrasch, Joerg; Klausner, James; AuYeung, Nick; Li, Like
Highlights: A continuum model for high-temperature thermochemical reactors is developed. Model validation with in-house measurement for a moving-bed reactor is presented. Radial temperature variation affecting reaction extent is captured in the 2D model. The 2D model shows better agreement with experimental results than the 1D model. The proposed model can provide guidance for reactor design, scale-up and optimization. Abstract: In this work, a continuum heat and mass transfer model coupling transport phenomena and high-temperature thermochemical reactions is developed for stationary packed-bed and counter-flow moving-bed reactors. After presenting the general modeling framework, we focus on the 2D axisymmetric version of the model for which validation is conducted with experimental results for a packed-bed reactor in the literature for manganese-iron oxide reduction/oxidation and an in-house counter-flow moving-bed reactor for magnesium-manganese oxide reduction up to 1450 °C. Transient simulation results including the local distributions of gas/solid temperatures, oxygen concentration and the extent of reaction, as well as the various energy flow components and energy conversion efficiencies are reported. The results based on the 2D axisymmetric model are also compared with those obtained from a previous 1D model. The comparison shows that capturing the radial variation is critical in reactor modeling and the 2D results demonstrate improved agreement with experiments. Specifically, large temperature variations along the radial direction are observed especially in the reaction zone; this non-uniform radial temperature distribution has a significant effect on the chemical reaction extent due to its strong dependence on temperature; and the overall oxygen concentration at the reactor exit and the predicted system efficiency are slightly lower in the 2D model compared to the 1D model. The present heat and mass transfer model can provide valuable insights into reactor design, scale-up, and operating conditions selection to maximize system energy storage efficiency.